Land Governance And Land Deals In Africa: Opportunities And Challenges In Advancing Community Rights - Rutherford, Blair (Journal of Sustainable Development Law and Policy, 2025)
This article examines the converging focus on “governance” by those donors and scholars who promote investment in land in Africa as well as by scholars and activists who criticize what they call “land grabs.” This focus on governance is particularly found in terms of understanding and assessing socio-economic consequences among the communities for the land deals, investment initiatives which have been accelerating on the continent over the last decade and longer. This article expands the concept of governance by examining how structures of authority and power are also involved in defining who belongs, or who has claims to belong, to these territories. It explores the topic of land deals and community rights through the conceptual lens of governance and belonging, the ability to be recognized as part of the community at various levels of action (including in terms of national citizenship). It starts with an examination of the recent increase in land investments in Africa, setting out its broad parameters, including public criticisms raised and some of the protests around them, and noting some of the key issues on which scholars have focused. In the next two sections, the article analyses these processes through the conceptual lens of governance and belonging as a way to bring out what the article proposes are key issues for assessing matters on community rights in regards to investments concerning natural resources in Africa, particularly over land. This analysis raises questions about those who uncritically promote Free and Prior Informed Consent as the solution to ensure “communities” approve any land deals.